2010
DOI: 10.4065/mcp.2009.0410
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcome of Klebsiella Species Bloodstream Infection: A Population-Based Study

Abstract: OBJECTIVE: To determine incidence rate, seasonal variation, and short-and long-term outcomes of Klebsiella species bloodstream infection (BSI) in a population-based setting. PATIENTS AND METHODS:We identified 127 unique patients in Olm sted County, Minnesota, from January 1, 1998, to December 31, 2007, who had Klebsiella spp BSI. Multivariable Poisson regression was used to examine temporal change and seasonal variation in incidence rate, and Cox proportional hazards regression was used to determine predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 24 publications
6
35
0
Order By: Relevance
“…This is similar to the incidence of 5.7 per 100,000 observed in Victoria, Canada, during 1998 to 2005 (5). In a study investigating Klebsiella species BSI from the United States (1998 to 2007), Al-Hasan and colleagues found overall incidence (including hospital-onset disease) rates of 15.4 per 100,000 for males and 9.4 per 100,000 for females (148). Among a cohort of 127 patients, 60 (47%) patients had community-acquired BSI (50 with Klebsiella pneumoniae, 9 with Klebsiella oxytoca, and 1 with Klebsiella ornithinolytica), and 53 (42%) had health care-associated BSI (46 with Klebsiella pneumoniae and 7 with Klebsiella oxytoca).…”
Section: Specific Etiologiessupporting
confidence: 63%
“…This is similar to the incidence of 5.7 per 100,000 observed in Victoria, Canada, during 1998 to 2005 (5). In a study investigating Klebsiella species BSI from the United States (1998 to 2007), Al-Hasan and colleagues found overall incidence (including hospital-onset disease) rates of 15.4 per 100,000 for males and 9.4 per 100,000 for females (148). Among a cohort of 127 patients, 60 (47%) patients had community-acquired BSI (50 with Klebsiella pneumoniae, 9 with Klebsiella oxytoca, and 1 with Klebsiella ornithinolytica), and 53 (42%) had health care-associated BSI (46 with Klebsiella pneumoniae and 7 with Klebsiella oxytoca).…”
Section: Specific Etiologiessupporting
confidence: 63%
“…The search revealed nine publications that reported differences between men and women with respect to incidence of BSI (Table 5, available online). [23][24][25][26][27][28][29][30][31] Controlling for a variety of covariates, three of the articles reported that men had significantly higher infection rates than women, and six reported no significant gender differences. Although the majority found no significant gender differences, the fact that all studies reporting significant differences found that males were at higher risk suggests a possible association.…”
Section: Discussionmentioning
confidence: 99%
“…The results for BSI are surprising, as previous findings suggest that 25-43 % of all BSIs originate from UTIs, which are more common in women than in men. [15][16][17] One possible explanation could stem from detection bias for UTIs, which might go undetected more often in men because they are thought to be less common (and thus looked for with less vigilance) and because men are less likely to have urinary catheters and thus urine cultures. 18 If UTIs are more likely to go undiagnosed and untreated in men, this could potentially lead to higher rates of BSI.…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenem-resistant K. pneumoniae (CRKP) infections may be associated with an increased rate of treatment failure and death [6], and the dramatic increase in the occurrence of CRKP worldwide aggravates this situation further [7]. Furthermore, older age, nosocomial infections, intensive care interventions, disease severity, and several comorbidities were reported to represent host factor contributing to the increased mortality rates of KP-BSI patients [3, 5, 8, 9]. Additionally, β-lactams were the first-line antibiotics selected for the treatment of KP-BSI patients, however, with the increase in the number of K. pneumoniae isolates producing extended-spectrum β-lactamase, the use of carbapenems increased as well.…”
Section: Introductionmentioning
confidence: 99%